Does the accuracy of case history affect interpretation of videolaryngostroboscopic exams?. (24th May 2019) - Sauder, Cara; Nevdahl, Martin; Kapsner‐Smith, Mara; Merati, Albert; Eadie, Tanya
Abstract : Objective: To determine the effect of initial diagnostic hypotheses on clinicians' 1) detection and perceived severity of abnormalities, and 2) clinical impressions and treatment recommendations for individuals with and without voice disorders following interpretation of videolaryngostroboscopy (VLS). Methods: Thirty‐two experienced speech‐language pathologists and otolaryngologists specializing in voice disorders read case histories prior to interpreting exams. Case histories suggested specific accurate or inaccurate laryngeal diagnoses, or a control scenario that suggested a normal larynx. The effects of the accuracy of case histories on perceived severity of associated visual‐perceptual parameters, clinical impressions, and treatment recommendations were examined. Results: Significant increases in perceived severity of posterior laryngeal appearance ( P < 0.05) and mucosal wave ( P < 0.02) were observed when these abnormalities were suggested by case histories. Overall agreement with clinical impressions improved from 49% to 72% when the case history was consistent with the examination. Case histories (accurate and inaccurate) indicating voice symptoms predicted recommendations for treatment above and beyond that of VLS presentation alone, P < 0.001. Conclusion: Case histories suggesting specific abnormalities significantly affected severity ratings for two of three associated visual‐perceptual parameters selected as primary outcome measures. Accurate case histories suggesting specific abnormalities increased the probability of detection and perceived severity. Inaccurate case histories led to false‐positive findings and failures to detect abnormalities or to interpret them as less severe. Case histories affected visual‐perceptual judgments and contributed to decisions about clinical impressions and treatment. Level of Evidence: 2b Laryngoscope, 130:718–725, 2020